Enterprise risk management analysis of GlaxoSmithKline Bangladesh Limited - Sadik, Khondaker Yaseer (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.